Analisis pembelajaran ppkn materi hubungan simbol dengan sila pancasila dalam penerapan nilai-nilai pancasila pada peserta didik kelas iv sd - Musyafiah, Afifatul; Mahfud, Hasan; Matsuri, Matsuri (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2022)
Abstract. The purpose of the study was to determine the implementation of Civics learning on the material "Relationship of Symbols with the Precepts of Pancasila'' and to find out the application of Pancasila values to fourth-grade students of SD Negeri Purwotomo No. 97. This research uses qualitative research using the case study method. The results of the study showed that Civics learning material on the relationship of symbols and Pancasila principles went well and learning took place actively. The implementation of the Pancasila values from the first to the fifth precepts has been going well, from the average results of 20 students or 92% of students have implemented the Pancasila values from the first to the fifth precepts, but there are still some values in the implementation that are not optimal, especially indicators. Opinions in the value of deliberation and representation have also not been carried out optimally because students are not confident in themselves and are afraid of being wrong if their opinion is not right. This there is a need for habituation carried out by parents and guidance by teachers in schools in the application of Pancasila values so that students are accustomed to behaving and behaving in accordance with Pancasila values.